Oral Hygiene and Gingival Health in Patients with Fixed Prosthodontic Appliances - A Six Month Follow-up - KC, Basnyat S; Sapkota, B.; Shrestha, S. (Kathmandu University Medical Journal, 2017)
Background Gingival inflammation and periodontal disease are the common complications of fixed dental prosthesis. They can be overcome by good oral hygiene maintenance. Objective The objective of this study was to assess the oral hygiene and gingival condition in patients after placement of fixed dental prosthesis for a period of six months. It was also analyzed how factors like type of fixed dental prosthesis (Single crown, fixed partial denture) and material (Metal, Porcelain fused to metal) are statistically associated with oral hygiene and gingival health. Method The sample consisted of 50 patients visiting the Dental Outpatient Department of Dhulikhel Hospital. The oral examinations were conducted using basic diagnostic tools (Mouth mirror, periodontal probe and explorer). Teeth and gingiva were examined using the Plaque and Gingiva Index by Silness and Löe. The examinations were conducted after 14 days and six months after placement of fixed dental prosthesis along with the oral hygiene instructions. Paired sample t-test were done to find statistical association using SPSS 16.0. Result Our results revealed no significant difference in plaque index among patients with single crown whereas fixed partial denture showed statistical significance. No significant differences were found for type of material. The statistical analysis showed similar results for gingival index. Conclusion Our research showed that single crown had no significant difference on Plaque index and Gingival index of the patient after 14 days and six months, whereas, Fixed partial denture showed significant difference. Both metal and porcelain fused to metal crown revealed no statistically significant difference on Plaque index and Gingival index.